Pengaruh Variasi Interlayer Terhadap Hasil Sambungan Material Dissimilar Menggunakan Mesin Las Gesek Rotary Tegak Bar Plate - Yohanes, Yohanes; Rafizan, Rafizan; Legisnal Hakim (Fakultas Teknik UMRI, 2024)
The aim of this research is to determine the effect of variations in interlayer thickness on welding time, interface area and hardness values ​​in dissimilar material welded joints using a bar-plate upright rotary friction welding machine. The method used in this research: rotational speed 2,613 rpm, friction pressure 0.5 MPa, forging pressure 0.7 MPa, forging time 10 seconds and interlayer variations (without interlayer, 0.3 mm, 0.5 mm and 1 mm). Tests used in the research: liquid penetrant test, metallography, and Vickers. It can be analyzed that interlayer variations have an effect on welding time. The time results obtained from using an interlayer with a thickness of 0.3 mm resulted in a time of 142.1 seconds, a 0.5 mm interlayer of 168.7 seconds, and a 1 mm interlayer of 204.4 seconds. The results for specimens without using an interlayer obtained a time of 71.3 seconds. The thicker the interlayer used, the longer the welding time. In observing the interface area, giving interlayer variations of 0.3 mm, 0.5 mm and 1 mm had an effect on cracks and cavities where all specimens were not found to have cracks or cavities, but voids were found in welding without allowing interlayer variations. In testing the hardness of interlayer variations with a thickness of 1 mm, the highest hardness was found in the interface area with an average hardness value of 169.56 VHN. Meanwhile, the lowest hardness value in the interface area results from variations without an interlayer with an average hardness value of 149.07 VHN